Effect of Intranasal Insulin on Cognitive Function in Diabetic Patients - Ding, Qiyang; Shi, Lei; Xia, Ji; Wang, Nisha; Gao, Wei (Journal of Contemporary Medical Practice, 2024)
A clear association between diabetes and cognitive impairment has been demonstrated in past studies, increasing the incidence of neurodegenerative diseases and accelerating the onset of Alzheimer's disease (AD) and other types of dementia. Many hypothesized mechanisms of diabetes leading to cognitive impairment exist, and the mechanism of insulin resistance has been demonstrated. Transnasal administration of insulin improves recall of spatial memory in healthy subjects in addition to verbal working memory, visuospatial working memory, delayed memory, and cognitive performance in cognitively impaired patients. No safety concerns have been identified in retrospective studies of intranasal insulin. This review aims to assess the potential of intranasal insulin as a treatment for cognitive impairment related to diabetes.